Chitosan-Zinc Oxide Composite for Active Food Packaging Applications - Razak, S.R. Abdul; Basri, H. (International Journal of Engineering and Technology, 2018)
Chitosan-zinc oxide (C-ZnO) films were prepared by a simple one pot procedure. In order to investigate the property of C-ZnO films, two composite films were prepared by varying the loading of ZnO and compared with pure chitosan film (C). The films were characterized by various techniques such as FTIR, DSC, tensile, contact angle and water vapour permeability. FTIR analysis showed changes in hydrogen bonds band at 3351 cm-1 compared to pure chitosan film. The incorporation of ZnO in chitosan films increased the contact angle by 30.5% in C-ZnO1.0 film while water vapour transmission rate decreased by 7.8% compared to C film. From the tensile test, C-ZnO0.5 and C-ZnO1.0 films were found to be much superior by 1.5 times and 2.5 times respectively compared to bare chitosan film. Larger inhibition ring (by 47%) was exhibited by C-ZnO1.0 as compared to C-ZnO0.5 when tested against S.aureus. From the results, it is displayed that the incorporation of zinc oxide to chitosan improve their properties which also shown the potential to become a candidate for food active packaging.